The Performance of Foodpanda: A Study of Customer's Perspective and Satisfaction in Malaysia and India - Kia Hui Gan; Thiam Yong Kuek; Kabir Rout; Nurul Nor Sharihan; Nurul Qanietah; Omar Omar; Yun Ru Ong (Journal of the Community Development in Asia (JCDA), 2022)
ABSTRACT This research paper aims to examine the performance of Foodpanda. Foodpanda is an online grocery and food delivery platform based in Berlin, Germany. Currently, it is the largest food delivery and grocery delivery platform in Asia. The objective of this paper is to study the perception and satisfaction levels of customers using Foodpanda and the service quality provided by Foodpanda. The impact of Covid-19 has affected the entire world and the reliance on food delivery apps has been doubled. Thus, the perception and satisfaction levels of users of Foodpanda and its services need to be explored and evaluated. The researchers collected the data using a structured questionnaire and a sample of 104 Foodpanda customers from India and Malaysia. The data examine the claims of Foodpanda regarding customer satisfaction and their perception of the market. The research shows that most people who ordered are satisfied with Foodpanda, including the delivery speed, price, and promotion.Keywords: Foodpanda, performance, customer perception, customer satisfaction.